Design, Synthesis, and Antileukemic Evaluation of a Novel Mikanolide Derivative Through the Ras/Raf/MEK/ERK Pathway - Rao, Qing; Xie, Kaiqiang; Varier, Krishnapriya M.; Huang, Lei; Song, Jingrui; Yang, Jue; Qiu, Jianfei; Huang, Yubing; Li, Yan; Gajendran, Babu; Li, Yanmei; Liu, Sheng (Frontiers in Pharmacology, 2022)
Chronic myeloid leukemia (CML) accounts for a major cause of death in adult leukemia patients due to mutations or other reasons for dysfunction in the ABL proto-oncogene. The ubiquitous BCR–ABL expression stimulates CML by activating CDK1 and cyclin B1, promoting pro-apoptotic and inhibiting anti-apoptotic marker expression, along with regulations in RAS pathway activation. Thus, inhibitors of the cyclins and RAS pathway by ERK are of great interest in anti-leukemic treatments. Mikanolide is a sesquiterpene dilactone isolated from several Asteraceae family Mikania sp. plants. Sesquiterpene dilactone is a traditional medicine for treating ailments, like flu, cardiovascular diseases, bacterial infections, and other blood disorders. It is used as a cytotoxic agent as well. The need of the hour is potent chemotherapeutic agents with cytotoxic effects inhibition of proliferation and activation of apoptotic machinery. Recently, ERK inhibitors used in clinics as anticancer agents. Thus, in this study, we synthesized 22-mikanolide derivatives that elucidated to be potent anti-leukemic agents in-vitro. However, a bioactive mikanolide derivative, 3g, was found with potent anti-leukemic activity, through Ras/Raf/MEK/ERK pathway. It can arrest the cell cycle by inhibiting phosphorylation of CDC25C, triggering apoptosis, and promoting DNA and mitochondrial damage, thus suggesting it as a potential chemotherapeutic agent for leukemia patients.